The Effect of Using Live Worksheet-Based Electronic Worksheets to Measure Cognitive Learning Outcomes - Muhammad Rusdan; Djem Bangun Mulya (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This study aimed to determine the effect of using live worksheet-based Electronic Student Worksheets (LKPD) to measure cognitive learning outcomes. This research approach uses quantitative research. The subjects in this study were students at Cimanggung State Senior High School class XI for the 2022/2023 academic year, totalling 72 respondents. The data collection method used in this research is a questionnaire method by giving questionnaires and tests to respondents as assessment material. The data analysis used was univariate and bivariate analysis through SPSS software. The results showed that the average value of the group given live worksheet-based LKPD was higher than the group that was not given live worksheet-based LKPD. The average value of the control class is 40.8 (low) to 66.7 (high). At the same time, the average value of the class given the treatment of giving Live Worksheet-based LKPD with a pre-test score (of 41.3), which means low, and a post-test score (of 75.7), which means very high. There is a significant difference in the effect of pre-test and post-test learning outcomes on students who use Live Worksheet-based LKPD in PPKn class XI SMA N Cimanggung lessons.